RANCANG BANGUN MESIN PEMBERSIH GULMA SEMI OTOMATIS - -, Paridawati; Suryasa, R Bagus; Raharjo, Arif; E, Riyan Ahmad (Jurnal Ilmiah Teknik Mesin, 2021)
Farmers in Indonesia currently still use traditional tools to cut weeds because they are cheaper. However, it has many drawbacks, including taking a long time and a lot of manpower. Therefore this research is to create a weed cleaning machine with a cheaper and more efficient cost. In the research, the design of the semi-automatic weed cleaning machine was carried out and after that the performance testing of the tool was carried out. From the test, it was concluded that in this study, a semi-automatic weed cleaning machine has been successfully built with an engine power of 401.9 W or 0.538 HP, 6.4 Nm of torque and gasoline. Semi Automatic weed cutting machine capable of cutting weeds for an area of 1 hectare takes an average of 34.7 hours with a manufacturing cost of Rp.2.225.000.